A construção de práticas docentes em alfabetização por professoras que assumem pela primeira vez turmas do 1º ano do ensino fundamental - Regina Aparecida Correa (2024)
This doctoral research aimed to analyze the construction of teaching practices in literacy by teachers who took on classes in the first year of elementary school for the first time. The specific objectives of the research were: 1) to describe and characterize the development of teachers’ practice who face, for the first time, a first-year elementary school class, regarding to literacy; 2) to understand how and based on which teachers who take on first-year elementary school classes, for the first time, guide their literacy practice. The research carried out has a qualitative, ethnographic approach, and used questionnaires, observations, interviews and document analysis as data collection instruments. Through a questionnaire applied with the help of the Municipal Department of Education, directors and coordinators of state and private schools in a town located in the south of Minas Gerais, two beginners teachers who taught for the first time were selected for a first-year elementary school class in2022. A total of 100 school days were observed, 50 days for each teacher, which corresponds to 200 class hours, and five interviews were carried out with each one of them. Throughout the observation, the researcher had access to lesson plans, textbooks, activities, posters, among others, which complemented and assisted in data analysis. As main theoretical references we have the following authors: Ana María Salgueiro Caldeira, Anne-Marie Chartier, Cecilia Fierro et. al, Elsie Rockwell, José Gimeno Sacristán and Ruth Mercado, for the concept of teaching practices; Magda Soares and Isabel Cristina Alves da Silva Frade, for teaching practices in literacy. The results indicate that the process of building teaching practices is dynamic and multifaceted. Among the main factors related to the construction of the two teachers' practices are, for example, historical factors, such as the teachers' life stories and their literacy process; personal factors, such as academicprofessional training and personal characteristics; contextual and material/institutional ones, such as curricular guidelines and pedagogical and school management, the context in which they worked, the public they served and the teaching materials they used. From these aspects, personal and contextual onesplayed a more relevant role in the teachers' practices. Although the two participating teachers in the research worked in the same institution and under similar conditions, the teaching practices constructed by them were very different. This heterogeneity seems to be related to the margin of autonomy and the idiosyncratic aspects that teachers have.